2014
DOI: 10.1111/nmo.12427
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacteria exert strain‐specific effects on stress‐related behavior and physiology in BALB/c mice

Abstract: These data show that these two Bifidobacteria strains reduced anxiety in an anxious mouse strain. These results also suggest that each bacterial strain has intrinsic effects and may be beneficially specific for a given disorder. These findings strengthen the role of gut microbiota supplementation as psychobiotic-based strategies for stress-related brain-gut axis disorders, opening new avenues in the field of neurogastroenterology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
227
3
10

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(254 citation statements)
references
References 107 publications
(302 reference statements)
14
227
3
10
Order By: Relevance
“…The results obtained in the elevated plus maze test among mice given E. faecium and L. rhamnosus supplements are in line with previous reports on the potential of probiotics to reduce an anxiety-like response in animal models (Bravo et al, 2011), which may be mediated through modulation of synaptic transmission as speculated previously (Diaz Heijtz et al, 2011). These findings suggest the psychobiotic potential of probiotics as speculated recently (Savignac et al, 2014). Nevertheless, comprehensive studies are further required to gain insights into the role of bacteria in modulating behavioural phenotypes.…”
Section: Discussionsupporting
confidence: 81%
“…The results obtained in the elevated plus maze test among mice given E. faecium and L. rhamnosus supplements are in line with previous reports on the potential of probiotics to reduce an anxiety-like response in animal models (Bravo et al, 2011), which may be mediated through modulation of synaptic transmission as speculated previously (Diaz Heijtz et al, 2011). These findings suggest the psychobiotic potential of probiotics as speculated recently (Savignac et al, 2014). Nevertheless, comprehensive studies are further required to gain insights into the role of bacteria in modulating behavioural phenotypes.…”
Section: Discussionsupporting
confidence: 81%
“…[90,96] Finally, different probiotic strains have been shown to reduce symptoms of anxiety and depression across several studies in clinical and healthy populations. [97,98] While there have also [5,9,10,88,90] Anxiolytic effects, sometimes sex-specific, in mice (light-dark box, elevated-plus maze) [72,113] Anxiolytic effects in mice (open field, defensive marble burying, elevated-plus maze, light-dark box) [91,93] Strain-specific anxiolytic effects in humans (e.g., Beck Anxiety Index, Hospital Anxiety & Depression Scale) and rodents (defensive marble burying, elevated-plus maze, open field) [11,62,133,134] Transplant from humans with depression or comorbid IBS and anxiety increases anxietylike behavior in mice (open field, step-down test, light-dark box) [96,125] Heightened anxiety in rats (open field) [89] Depression Increased depressive-like behavior in mice (forced swim) [90] Increased depressive-like behavior in rats (forced swim) [94] Antidepressant effects in mice and rats (forced swim, tail suspension, learned helplessness after inescapable shock) [91,92] Strain-specific antidepressant effects in humans (e.g. Beck Depression Inventory, Hospital Anxiety & Depression Scale) and rodents (tail suspension test, forced swim, sucrose preference) [11,97,98,133,134] Transplant from depressed human donors induces depressive-like behavior in mice (sucrose preference, forced swim [varied results], tail suspension test) [90,96] Learned fear Impaired fear recall in adult mice [101] Acute administration enhances fear extinction in rodents and exposure therapy in humans, [103,104] reduces fear recall in huma...…”
Section: Anxiety-and Depression-like Behavior Are Regulated By Gut MImentioning
confidence: 99%
“…A number of proof-of-principle studies in healthy human volunteers have demonstrated that multistrain probiotics, fermented drinks containing probiotics, or prebiotics, can alter resting brain activity, cognitive performance, baseline physiological stress outputs and self-reported psychological variables (Benton et al, 2007;Chung et al, 2014;Messaoudi et al, 2011;Mohammadi et al, 2015b;Schmidt et al, 2015;Steenbergen et al, 2015;Tillisch et al, 2013). More recently, Bifidobacterium longum 1714, selected based on pre-clinical evidence (Savignac et al, 2014;Savignac et al, 2015), was shown to reduce stress levels and to produce a neurocognitive profile associated with enhanced memory in healthy volunteers (Allen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%